Developing Value Based Services for Indonesian Microtakaful - Firdaus, Achmad (LPPM IAIN Kudus, 2019)
Otoritas Jasa Keuangan (OJK) found that the poor and low income people were reluctant to join as insurance participants. OJK has conducted many socialization activities about microinsurance for low-income people which aimed to increase their literacy of insurance. SMES (Sederhana – Mudah – Ekonomis – Segera) services aim to increase insurance inclusion. The study aims to propose a model of value-based service on microtakaful. The service refers to SMES (Sederhana – Mudah – Ekonomis – Segera) and Maslahah Performa value. SMES value to explain the value expected by takaful participants. Maslahah performa to explain the fulfillment of needs to sharia demands by takaful operator. The SMES variable is developed into various sub variables according to SEOJK. Maslahah performa is elaborated to get worship orientation variables and internal process orientation which then be developed into various sub variables. The sub-variable weight is determined according to the importance level of each sub variable. The research finds that a value-based microtakaful service model can be derived from the SMES approach and maslahah performa. There is a linkage between the value-based microtakaful service according to participant expectation and spirituality and sustainability. The reasearch will contribute to increase literacy of microinsurance.